Reconstruction of Hind and Mid-Foot Defects after Melanoma Resection Using the Reverse Sural Flap: A Case Series - Larrañaga, Juan Jose; Picco, Pedro Ignacio; Yanzon, Alejandro; Figari, Marcelo (The Surgery Journal, 2017)
Background Melanoma resection creates important soft tissues defects, which are difficult to manage when located on the weight-bearing heel and mid foot. There is little evidence on the use of the reverse-flow sural flap for this type of reconstruction.Objective This study reports our case series on the reconstructive management of the hind and mid-foot defects after melanoma resection using the reverse sural artery flap.Materials and Methods This is a retrospective study of four consecutive patients treated with resection of melanoma of the feet and reconstruction with reverse sural artery flap from 2006 to 2009.Results The mean age of the patients was 54 years, three were females, and one was male. Three of the defects were located on the weight-bearing heel, the other on the mid-foot dorsum. The melanomas were fully resected with wide margins. Three patients were reconstructed primarily, whereas one patient was reconstructed 4 weeks after the resective surgery. This series revealed 100% flap survival and there was no partial necrosis. Major complications were not observed. The four patients completely recovered the function of the affected limb.Conclusion The reverse sural flap is a viable option for the reconstruction of foot defects after melanoma resection.
Keywords: reverse sural flap; foot melanoma; heel reconstruction; sural flap; neurocutaneous flap